COMMENTS ON THE PROGRESS ON THE APPLICATIONS OF RE-OS ISOTOPIC STUDY ON THE OPHIOLITES - Shi R.D.; Zhi X.C.; Chen L.; Ding B.H. (My University, 2006)
Re-Os isotopic systematics is the best tracer on studying the ophiolitic peridotite because, in contrast with the geochemical properties of Sm-Nd, Rb-Sr, U-Th-Pb and Lu-Hf, all of which are incompatible elements, Os is a compatible element in most mantle melting processes, so that it generally remains in the mantle, whereas the much more incompatible Re is extracted and enriched in the melt. This system therefore provides information that is different from, and complementary to, what we can learn from Sm-Nd, Rb-Sr, U-Th-Pb and Lu-Hf. Four points of progress have been made on the application of Re-Os studying on the ophiolite. First, determining the Re-Os characteristics of the ophiolite in which peridotites are low Re/Os and 187Os/188Os ratios, whereas lavas are high Re/Os and 187Os/188Os ratios; Secondly, dating of PGM within the ophiolitic chromitite by Re depleted ages supports the idea that the complicated ultramafic rocks of ophiolite are produced by multistage partial melting of mantle; Thirdly, measuring187Os/188Os of MORB and the sulfides in abyssal peridotites (AP) indicate that there is no gap between the MORB and the most AP with higher 187Os/188Os ratios than DMM (0.1246), and gap still occurring between MORB and some AP with lower 187Os/188Os ratios than DMM, namely, Re-Os study on the ophiolite provides a new constraining on the geochemical relations on the residual peridotites and lavas; Finally, revealing that the ophiolitic peridotites contain the older sub-continental lithospheric mantle (SCLM), this case is not previously known before Re-Os analyzing. Although the Re-Os isotope made progresses on studying the ophiolite, more problems, such as dating the Phanerozoic ophiolitic peridotites, still want to be done further work due to the short time of application of Re-Os study on the ophiolite.
Keywords: DEPLETED MANTLE; OPHIOLITE; PRIMITIVE UPPER MANTLE; RE DEPLETED AGE; RE-OS ISOTOPE